Measuring the impact of leverage indicators on market returns of listed companies An Empirical Study - األسخاذ امىساغد امدكخِر وحىد أةكر أحىد وحىد; األسخاذ امىساغد امدكخِر غىر امسر امحسي وحىد (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
The study aimed to measure the impact of leverage indicators (debt to total assets and equity, equity to assets, non-current interest and liability coverage ratio to assets and current liabilities to assets) in the returns of shares of companies listed on the Saudi Stock Exchange during the period 2012- 2015. Through the multiple regression analysis model, the statistical results revealed that all independent variables explain a change of 52.7% of the change in the independent variable stock returns at a confidence level of 95%. As well as acceptance of the alternative assumption of five independent variables: (debt to total assets and equity, equity to assets, non-current liabilities to assets and current liabilities to assets) where the value of the moral level was less than 0.05 at 95% confidence level. And the acceptance of the imposition of zero for one variable and the index of interest coverage, and recommended the study of the need to pay attention to the indicators of financial leverage before the decision to invest in shares listed companies in the stock market and interest analysis of the index of interest coverage because it reflects the value of interest paid by the company in return for financing loans (non-subjective).